Hidden Magnetic States Emergent Under Electric Field, In A Room Temperature Composite Magnetoelectric Multiferroic. Issue 1 (December 2017) - Clarkson, J.; Fina, I.; Liu, Z.; Lee, Y.; Kim, J.; Frontera, C.; Cordero, K.; Wisotzki, S.; Sanchez, F.; Sort, J.; Hsu, S.; Ko, C.; et al.
Abstract The ability to control a magnetic phase with an electric field is of great current interest for a variety of low power electronics in which the magnetic state is used either for information storage or logic operations. Over the past several years, there has been a considerable amount of research on pathways to control the direction of magnetization with an electric field. More recently, an alternative pathway involving the change of the magnetic state (ferromagnet to antiferromagnet) has been proposed. In this paper, we demonstrate electric field control of the Anomalous Hall Transport in a metamagnetic FeRh thin film, accompanying an antiferromagnet (AFM) to ferromagnet (FM) phase transition. This approach provides us with a pathway to "hide" or "reveal" a given ferromagnetic region at zero magnetic field. By converting the AFM phase into the FM phase, the stray field, and hence sensitivity to external fields, is decreased or eliminated. Using detailed structural analyses of FeRh films of varying crystalline quality and chemical order, we relate the direct nanoscale origins of this memory effect to site disorder as well as variations of the net magnetic anisotropy of FM nuclei. Our work opens pathways toward a new generation of antiferromagnetic – ferromagnetic interactions for spintronics.